Localités et historiographie. Le débat sur l'histoire de Sanremo au xviiie siècle - Vittorio Tigrino (Les Dossiers du GRIHL)
This work is focused on a case, the one which oppose in the 18th century the government of the Republic of Genoa to a community of its territory, Sanremo. The conflict starts in 1729, from the resistance of Sanremo to the extension of certain general laws for the commerce, and after 1753 it develops itself on the international plan, with very strong rebounds in the diplomatic relationships between the Republic and the European courts. The case sheds light on the strategy of the imperial claim advanced by a part of the representative of the Sanremo community, who finds collaboration among certain imperial officials, long-time defenders of the reason and the imperial superiority over all the Republic.The case arises an intense historical and juridical production which concretises itself in a great number of printed and written works. It offers an interpretation of history of relationships between the two towns, where the juridictional clarifications shuffle with the claim for an historical identity and a local political legitimization.Controversies similar to those are indeed strategic observer to measure in which way the local initiative meets and conditions the redefining of the political, juridical and economic categories (and this sends back to the strategic importance of reading and interpretation of a fact in a local, analytical scale). The recourse to the contextualisation, in the archive, allow to catch in a better way the complex relationship between the formalization of the printing works and the concrete action of the opposite parties, and to show the dynamics of the litigation which, in a general point of view, are hardly perceptible. Starting from certain archive references makes it effectively possible to catch clearly the moments and the ways by means of which this ‘imperialità’ of Sanremo was invented and built, and how the Genoese side opposed itself to this reading of the past, without however preventing the creation of a real chain of references and of legitimation (a ‘bibliographic chain’) which allowed some deformed reconstructions, if not entirely invented, to find some fertile land in historiography.